Analisis Perbedaan Keuntungan Usaha Kopra Menggunakan Metode Penjemuran dan Metode Pemanggangan di Desa Lefuto Kecamatan Kaledupa Kabupaten Wakatobi - Oktaviati, Nur; Dirgantoro, Muhammad Arief; Sadimantara, Fahria Nadiryati; Abdi, Abdi (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
This study aims to determine: (1) the amount of business profits copra drying method and the method of roasting in the village of the District Lefuto Kaledupa Wakatobi and (2) differences in business benefits copra drying method and the method of roasting in the village of the District Lefuto Kaledupa Wakatobi. The results showed that (1) Average profit among business copra drying using Rp14,358,396/month and copra business using the roasting method Rp 7,089,732/month. (2) Based on the results of the t test is known that the average profit businesses using methods of drying copra and copra business using the roasting method has significant advantages difference.